Numerical Study of Vortex Effect on Splitter Plate under Turbulence Flow over Circular Cylinder - Sambu, Mathan; BIN ZAMAN @ BUJANG, PROF. MADYA Dr. IZZUDDIN; BIN MANSHOOR, PROF. MADYA Ir. Ts. Dr. BUKHARI; Tai, Vin Cent; Muniandy, Nagentrau (Journal of Advanced Mechanical Engineering Applications, 2024)
Vortex shedding is commonly observed in both natural and artificial situations. Two key variables where the blockage ratio and the Reynolds number determining the flow characteristics around a confined bluff body. The goal of the current study was to apply numerical simulation to examine the development of vortices in a continuous turbulence flow at distanced position of single splitter plate. As a starting point, the flow around a fixed circular cylinder and plate is examined at various spaced positions ratios, where *L ratios are defined as the distance between the cylinder's centre and the plate's front edge. In the wake of the cylinder, when *L is raised, positive and negative vortices are generated. The pressure distribution following the vortex shedding core strike is felt at the plate face tip (starting edge). Compared to the other two positions, the CL created by L2 is larger and receiving better cortex hit.